The Influence of Online Learning on Students' Learning Interests during Covid-19 - Erika Ambarita; Runi Fazalani; Ida Bagus Benny Surya Adi Pramana; Ronny Massie; Gusti Yohanis Sette (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to find out the influence of learning among students during the pandemic. This research uses qualitative research methods. Qualitative research is research that is descriptive and tends to use analysis. Data collection techniques are interviews and literature. Data sources from the community around the research house, books, journals, newspapers. This data analysis technique is a reference technique obtained during research such as research journals, respondents' answers. The result of this study is that online learning has an impact on students' learning interests because students get bored easily when studying online. Learning that is not very pleasant is not like learning in the classroom. Therefore, teachers must create interesting online learning and increase students' learning interest. A method to develop students' learning interests by providing learning motivation to students with positive words and fostering students in learning conditions.